Study on Spatio-temporal Distribution of Chlorophyll-a on Pelagic Catch Productivity in Muara Bendera, West Java, Indonesia - Setiawan, Heri; Manessa , Masita Dwi Mandini; Supriatna (Jurnal Ilmiah Perikanan dan Kelautan, 2024)
Graphical Abstract Highlight Research The trend of chlorophyll-a in the pelagic fish catchment area of the Muara Bendera has increased. Trend of chlorophyll-a values around the waters of the Citarum and Cisadane River Estuaries increased. Chlorophyll-a and pelagic CPUE have a negative relationship. The waters around the mouth of the Citarum River are mesotrophic - eutrophic waters Abstract Chlorophyll-a has been considered an indicator of pelagic fish abundance in waters. Although a high nutrient load causes eutrophication, leading to fish mortality, global-scale climate anomalies will also influence the oceanographic conditions of the seas. This study aimed to investigate spatial patterns and trends of chlorophyll-a, the relationship between chlorophyll-a and pelagic fish catch productivity, and the effect of ENSO and IOD on pelagic fish catch productivity. The chlorophyll-a data were obtained from the SeaWiFS and Terra-Aqua MODIS time-series datasets of ocean color satellites. The results indicated that Jakarta Bay had the highest chlorophyll-A concentration. The Chlorophyll-A concentrations declined as the distance between the estuary and the coast grew. From 1997 to 2021, the regional pattern of increasing chlorophyll-a concentrations in the Citarum and Cisdane estuaries was continuous. Since 2001, the concentration of chlorophyll-a in Jakarta Bay has declined, whereas it has begun to climb in the seas of the North Seribu Islands. The increasing chlorophyll-A trend in the Seribu Islands is attributed to rising nitrate levels induced by human-driven coral degradation. Between 1997 and 2021, the concentration of chlorophyll-a in the Muara Bendera fishing region grew by +0.013 mg/m3/year, or 1.43 percent each year. The correlation between chlorophyll-a and pelagic fish catch productivity was -0.13. ENSO does not affect the productivity of pelagic catches in this region. However, it was discovered that IOD reduced the productivity of low-category pelagic catches.